A NOVEL APPROACH TO INTRALESIONAL AUTOLOGOUS SERUM THERAPY IN MELASMA: AN OPEN-LABEL, PROSPECTIVE STUDY - RAKESH KUMAR MEENA; SAGAR, VIVEK; SHARMA, SUDHANSHU; PANDEY, DHRUVENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The study aimed to assess the effectiveness of intralesional autologous serum therapy in Melasma. Methods: A total of 30 patients over 18 years of age were enrolled in the study with prior approval from the institute’s ethical committee. Serum was injected intradermally into the melasma lesions of the patient every 2 weeks with a 30G insulin syringe. Patients were called for follow-up every 15 days until 90 days. On each visit, clinical response to treatment was calculated using the modified Melasma Area and Severity Index (mMASI) score, and side effects were also noted, if any. Results: The reduction in mean mMASI score from baseline was not significant till the second visit (day 15) (p=0.317), while it was statistically significant from the third visit onwards (day 30) (p=0.024). The reduction in mean mMASI score from baseline 3.95±3.23 to 2.31±2.16 (41.51% improvement) is suggestive of a good response, which was also statistically significant (p≤0.001). Conclusion: Study patients perceived a significant improvement in pigmentation during the therapy period without any considerable side effects. Thus, autologous serum therapy may be a viable alternative to the existing treatment modalities for Melasma.